Penyelesaian Perkara Anak Sebagai Pelaku dan Korban Ditinjau Dari Asas Kepentingan Terbaik Bagi Anak - Hadibah Zachra Wadjo; Elias Zadrach Leasa; Denny Latumaerissa; Judy Marria Saimima (Faculty of Law, Universitas Pattimura, 2020)
In reality, specifically for the principle of the best interests of children who are accommodated in the Aanak Criminal Justice System Act not yet maximized to be applied in cases of children who are dealing with the law both against children as perpetrators and children as victims, which in the settlement of losses suffered by children as a victim of a criminal offense, it has not been concretely felt. Based on the explanation above, the problem that the writer wants to analyze is Is the settlement of the case of children considering the best interests of the child as the perpetrator and the child as the victim? Constraints in fulfilling the best interests principle for children as perpetrators and children as victims. The research method used is a type of empirical juridical research. The results showed that the fulfillment of the best interests of children in the case of children in conflict with the law must be supported by all relevant stakeholders so that children's rights can be implemented at all stages of the case inspection in accordance with the mandate of the Aanak Criminal Justice System Law and the Law related, it is not enough there, the fulfillment of the best interests must also continue to be supported back to the community. Obstacles in fulfilling the best interests of cases of children in conflict with the law, namely the lack of investigators for the protection of women and children, inadequate facilities or infrastructure, human resources both for women and children protection investigators and for assisting victims who are not yet qualified, lack of budget in case settlement children in conflict with the law.